Comparison and combination effects on antioxidant power of curcumin with gallic acid, ascorbic acid, and xanthone - Naksuriya, Ornchuma; Okonogi, Siriporn (Drug Discoveries & Therapeutics, 2015)
Curcumin has been extensively reported as a potential natural antioxidant. However, there was no data on activity comparison as well as the biological interactions of curcumin with other natural antioxidants. The aim of the present study was to investigate the antioxidant power of curcumin in comparison with three important natural antioxidants; gallic acid, ascorbic acid, and xanthone on free radical scavenging action and their combination effects on this activity. The results indicated that the activities of these compounds were dose-dependent. The 50% effective concentration (EC50) of curcumin was found to be 11 μg/mL. Curcumin showed significantly higher antioxidant activity than ascorbic acid and xanthone but less than gallic acid. Interestingly, curcumin revealed synergistic antioxidant effect when combined with gallic acid whereas the antagonistic effect occurred in curcumin combination with ascorbic acid or xanthone. These results suggest that curcumin-gallic acid combination is the potential antioxidant mixture to be used in place of the individual substance whereas using of curcumin in combination with ascorbic acid or xanthone should be avoid.